Effective control in MSI-high unresectable intrahepatic cholangiocarcinoma treated with gemcitabine/cisplatin/durvalumab and proton beam therapy: a case report - Nosaka, Takuto; Naito, Hironori; Murata, Yosuke; Akazawa, Yu; Tanaka, Tomoko; Takahashi, Kazuto; Naito, Tatsushi; Ohtani, Masahiro; Imamura, Yoshiaki; Nakamoto, Yasunari (Frontiers in Immunology, 2025)
Systemic chemotherapy is the standard treatment for unresectable intrahepatic cholangiocarcinoma (iCCA); however, its efficacy remains limited. We report a clinically valuable case of a 57-year-old woman with advanced unresectable iCCA characterized by high microsatellite instability (MSI-high) and major vascular invasion. The patient presented with purpura and was diagnosed with MSI-high iCCA with intravascular tumor extension reaching the right atrium and regional lymph node metastases. Combination therapy with gemcitabine, cisplatin, and durvalumab (GCD therapy) was initiated, resulting in a 56% reduction in tumor size after eight cycles. To enhance local tumor control, proton beamtherapy (3.3 Gy × 22 fractions) was added, which was completed without adverse events. The patient subsequently received durvalumab maintenance therapy, followed by pembrolizumab. Although there was minimal growth of lymph node and pulmonary metastases, no regrowth of the intrahepatic primary tumor was observed for 18 months after PBT. This case illustrates the potential clinical value of combining GCD therapy with proton beam therapy for MSI-high, unresectable iCCA with major vascular invasion. The combination achieved systemic disease control and durable local control without significant toxicity.